Ab-initio study about the electronic, optical and thermoelectric nature of α-, β-, and γ-phases of CdS semiconductor: using the accurate m-BJ approach. (24th February 2021) - Salman Khan, Muhammad; Gul, Banat; Khan, Gulzar; Benaadad, Merieme; Ghlamallah, Benabdellah; Ali Khattak, Shaukat; Khan, Tahirzeb; Zulfiqar, Syed; Shah, Said Karim; Adil Khan, Muhammad
Abstract: In this work the first principles-based calculations with the FP-LAPW (full potential linear augmented plane wave method) are employed to investigate structural, thermal and optoelectronic properties of the three different phases of CdS binary compound. Our electronic band structure calculations display a direct type band transition with a gap value (Γv − Γc ) equal to 0.9 eV, and 1.2 eV for β and γ phases respectively. Due to inexistence of VBM (valence band maxima) and the CBM (conduction band minima) located at the same Γ-point an indirect band transition was predicted in case of α -phase. Our calculated T-DOS and P-DOS visualizes to be shifted successively towards higher values along the energy axis. The σ s−p bonding character in the V/B is responsible for the instigation of relatively localized states S-p, Cd-d and Cd-p states close to Fermi energy. We also computed and discussed the important optical constants like the complex dielectric constant components, electron energy loss functions, reflectivity spectra, the absorption coefficients, refractive indices, real component of optical conductivity and the extinction coefficient. The inter band contribution resulting due to the corresponding optical nature was also studied and discussed in detail for these three phases. The temperature dependent thermoelectric parameters were studied to explore the thermoelectric behaviour. The thermoelectric parameters like thermal conductivity, Seebeck coefficient, specific heat capacity, Power factor, Electrical conductivity, Susceptibility and figure of merit of the three phases are investigated for their possible thermoelectric applications. The present work could be concluded as a theoretical qualitative type calculation related to optoelectronic and thermoelectric nature of the three studied phases and their efficient device application.